How Spanish Journalists consider minorities and vulnerable groups should be treated by media - Zalbidea Bengoa, Begoña; Pérez Fuentes, Juan Carlos; Urrutia Izaguirre, Santiago; López Pérez, Susana (Estudios sobre el Mensaje Periodístico, 2012)
The majority of the general European codes include among their principles that professionals have a duty not to discriminate for reasons of sex, of etnia (or of race) and of religion. Some texts go beyond and speak about the national, cultural or social origin, language or ideology. This study focuses on how much are assumed these guidelines in the professional activity of journalists from four regions (autonomous communities) that add up to more than half of population of Spanish state (52 %): Andalusia, Catalonia, Madrid and Basque Country. The discrimination affects often to groups that are socially or economically deprived or marginalized -as immigrants, women, homosexuals, disabled and elderly peopleand, besides the usual questions that arise in this area, news people are faced with the issue whether is it admissible to act with some kind of ‘positive discrimination’.
Keywords: Ethics; deontology; journalists; journalism; discrimination; deprived groups.